2016
DOI: 10.1002/ajhb.22925
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of modern human longitudinal body and transverse shoulder proportions

Abstract: The ontogeny of transverse shoulder proportions is more complex than what is observed for bi-iliac breadth, suggesting that transverse shoulder to limb proportions are not solely influenced by ecogeographical conditions. Our analysis demonstrates that methodologies that incorporate critical dimensions of body form could shed new light on human adaptation in both paleontological and neontological contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…It must be noted that sample sizes, particularly for distal, lower limb elements, are much less than those of upper limb elements and femora. Despite this variation in sample size across elements and indices, these sample sizes are still robust compared with other skeletal studies of fetal remains (e.g., Bleuze et al, ; Frelat et al, ; Frelat & Mittereocker, ; Temple et al, ). Individuals of African ancestry display greater index values than those of European ancestry for brachial and crural indices, indicating a greater relative length of the distal elements compared with the proximal elements.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It must be noted that sample sizes, particularly for distal, lower limb elements, are much less than those of upper limb elements and femora. Despite this variation in sample size across elements and indices, these sample sizes are still robust compared with other skeletal studies of fetal remains (e.g., Bleuze et al, ; Frelat et al, ; Frelat & Mittereocker, ; Temple et al, ). Individuals of African ancestry display greater index values than those of European ancestry for brachial and crural indices, indicating a greater relative length of the distal elements compared with the proximal elements.…”
Section: Resultsmentioning
confidence: 97%
“…Researchers who have explored the origins of ecogeographic variation among adults by studying the postnatal period have detected population differences in body proportions (Bleuze et al, ; Cowgill et al, ; Frelat et al, ; Frelat & Mittereocker, ; Hadley & Hruschka, ; Temple et al, ). Much of this research notes that limb proportions fluctuate over development, with interpopulation variation in limb proportions being detected early on and achieving adult form with the onset of puberty (Bleuze et al, ; Cowgill et al, ; Frelat et al, ; Temple et al, , ). Cowgill et al () found population differences at less than 1 year of age that remained relatively consistent over the course of development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations